Responsibilities of Notaris/PPAT in Credit Agreements & Deed on Granting of Liability Rights (APHT) When the Debtor is in Default - Muhammad Hudallah; Anis Mashdurohatun; Widhi Handoko (Sultan Agung Notary Law Review, 2022)
This research aims to know that in the current era of industrialization, credit is something that is not far from everyday life. For the community, both wealthy and underprivileged, credit is a solution to meet the needs of people's lives such as: clothing, food, housing. One of the important credit principles is collateral. In credit activities that occur in the community, it can be noted that generally it is often required to provide credit guarantees. Credit guarantees will have several functions and one of them is securing credit repayment if the debtor is in default. Credit guarantees have an important role in securing bank refunds. The method used in this research was a sociological juridical approach. A sociological juridical approach was an approach by looking at a legal reality in society. Land is one of the immovable objects that are widely used as collateral for loan repayment. Mortgage rights over land are often used to obtain credit facilities because land has a high economic value and always increases from time to time. Land rights as collateral in agreements between creditors with the Debtor can be bound by using Mortgage Rights. The result show that the role and function of a notary/PPAT is important in assisting the government and other parties in need to provide certainty, order and legal protection in making authentic deeds and registration of Mortgage Rights until a certificate is issued by the Land Agency.